2009
DOI: 10.1002/jgm.1406
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of nuclear plasmid DNA delivery is a critical determinant of transgene expression at the single cell level

Abstract: Background The nuclear envelope that encloses the nucleus is a significant barrier to non-viral vectors and shrouds the relationship between the trafficking of plasmid DNA to the nucleus and expression of an encoded transgene. Here, we use a novel single cell approach to quantify nuclear import of plasmid DNA following non-viral transfection and correlate this with reporter gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 34 publications
6
60
1
Order By: Relevance
“…Since it has been shown that that the amount of DNA delivered to the nucleus is amplified at increasing extracellular DNA concentration (Glover et al 2010;Tachibana et al 2002), we hypothesized that a higher intranuclear DNA concentration might be achieved by adding non-coding DNA to increase total extracellular DNA concentration, which could finally lead to a concomitant increase in protein expression. We showed that the use of carrier DNA in the form of IgG conc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it has been shown that that the amount of DNA delivered to the nucleus is amplified at increasing extracellular DNA concentration (Glover et al 2010;Tachibana et al 2002), we hypothesized that a higher intranuclear DNA concentration might be achieved by adding non-coding DNA to increase total extracellular DNA concentration, which could finally lead to a concomitant increase in protein expression. We showed that the use of carrier DNA in the form of IgG conc.…”
Section: Discussionmentioning
confidence: 99%
“…fraction of cells which have received the DNA, influence the culture productivity. Both these factors (transfection efficiency and DNA delivered) are affected by the concentration of plasmid DNA in the culture (Glover et al 2010). It has also been shown that the amount of DNA delivered to the nucleus is a nonlinear function of the extracellular DNA concentration, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large scale transfections require producing and purifying large amounts of plasmid DNA in E. coli. Efforts to decrease plasmid requirement have used non-linear relationship between amount of DNA delivered to the nucleus and extracellular DNA concentration, along with saturation kinetics of transgene expression as a function of intranuclear plasmid availability 31,32 . We have showed that the supplementation of plasmid DNA with non-coding DNA to increase extracellular DNA concentration, increases the transfection efficiency and TGE yield per unit plasmid 33 .…”
Section: Host Cells and Host Cell Engineeringmentioning
confidence: 99%
“…Possible causes of transgene expression variability include differences in the number of integrations, transgene inactivation, or different genome integration sites of the vector. Transgene expression critically depends on the number of plasmids entering the nucleus (James & Giorgio, 2000;Glover et al, 2010), which not only depends on the ability of vectors to deliver intact DNA but also on the type of cell, as some cells translocate plasmid DNA from the cytoplasm to the nucleus more efficiently than others (James & Giorgio, 2000). However, high copy numbers of the transgene can increase methylation pattern of the promoter and thereby inducing transgene silencing (Garrick et al, 1998).…”
Section: Transgene Expressionmentioning
confidence: 99%